Pemberdayaan Masyarakat melalui Pengembangan Produk Olahan Keripik Pisang Talas di Desa Mamantang Kabupaten Balangan - Nahl, Firya Zafieren; Damaiyanti, Varinia Pura; Putri, Desta Emelyya; Madani, Gusti Ahmad Affan; Raihan, Achmad; Ramadhan, Akhmad; Lestari, Ermida; Sari, Nia Novita; Aulia, Nur Wita; Safitri, Aida; Dewi, Ariana; Habibi, Ahmad Wildan (Prodi Sosiologi FISIP ULM, 2025)
This community service project was carried out in Mamantang Village, Halong Subdistrict, Balangan Regency, South Kalimantan, with the aim of improving the skills and economy of the community through training in making taro chips. Mamantang Village is an agricultural area with taro as its main crop, but until now, taro has only been sold in its raw form with low economic value. The main problems faced by the Mamantang Village community are a lack of knowledge in processing agricultural products and limited access to technology and markets. The activities carried out by the community service team used participatory and learning-by-doing methods, involving the community directly in every stage of the activity, from socialization, technical training, production, to product marketing. The training on making banana chips was attended by the community, especially the women of the PKK, with a focus on making two flavors of taro banana chips, namely sweet and spicy and palm sugar, which are characteristic of Mamantang Village. The results of the activity showed a significant increase in the community's skills and knowledge regarding processing techniques, packaging, and marketing strategies for processed products. The community has begun to recognize the importance of innovation and the added value of local products in increasing family income. This program also succeeded in producing 50 packages of taro banana chips under the brand name “Sasangan Mamantang” as the village's flagship product. Overall, this activity has had a positive impact on the development of a creative economy based on local potential and is expected to become a model for sustainable rural community empowerment